Making Decisions about How to Solve Nonlinear Dynamical Systems of the Kannan Type in a New Complex Function Space of Formal Power Series. (31st January 2023) - Alsolmi, Meshayil M.; Mustafa, Arafa O.; Mohammed, Mustafa M.; Bakery, Awad A.
Abstract : The sufficient settings of the space generated by absolute type-weighted gamma matrices of rank p in the Nakano complex functions of the formal power series, as well as its associated prequasioperators' ideal equipped with definite functions, are defined and explained in this paper. Assorted prequasinorms are shown to have the Fatou characteristic. Some of its geometric and topological features and the prequasioperators' ideal that goes with it are talked about. These structures have a relationship with the fixed points of the Kannan contraction and nonexpansive mappings. By looking at real-world examples and how they are used, it is shown that there are solutions for nonlinear dynamical systems of the Kannan type.